Abilities to exploit newly-acquired technologies as a source of competitive advantage of finance companies in Poland = Zdolności do eksploatowania nowo pozyskiwanych technologii jako źródło przewagi konkurencyjnej przedsiębiorstw finansowych w Polsce - Glabiszewski, Waldemar; Grego-Planer, Dorota (Zielona Góra: Faculty of Economics and Management Press)
The article of empirical nature is an attempt to evaluate the influence of the abilities to exploit newly acquired technologies possessed by finance companies operating in Poland on the competitive advantages they gain.
Keywords: przedsiębiorstwa finansowe; potencjał absorpcyjny; transfer technologii; przewaga konkurencyjna; zdolności; finance companies; absorptive capacity; technology transfer; competitive advantage; abilities